Citrus fruit processing - Berk, Zeki (Academic Press, 2016)
Citrus Fruit Processing offers a thorough examination of citrus—from its physiology and production to its processing, including packaging and by-product processing. Beginning with foundational information on agricultural practices, biology, and harvesting, Citrus Fruit Processing goes on to describe processing in the context of single-strength juices, concentrated juices, preserves, and nutrition. New technologies are constantly emerging in food processing, and citrus processing is no different. This book provides researchers with much-needed information on these technologies, including state-of-the-art methodologies, all in one volume.--Provided by publisher.